AB0398 Responsiveness of a generic and disease specific health related quality of life questionnaire in patients with systemic lupus erythematosus. (23rd January 2014) - Devilliers, H.; Amoura, Z.; Audia, S.; Jolly, M.; Bielefeld, P.; Arnaud, L.; Binquet, C.; Besancenot, J.-F.
Abstract : Background: Little is published on comparative responsiveness of generic and disease specific Patients reported outcomes (PRO) tool in systemic lupus erythematosus (SLE). Objectives: To determine and compare the responsiveness and minimally clinical important difference (MCID) of a generic and disease specific PRO measure in SLE. Methods: SLE patients from a French multicenter study were clinically assessed for activity (SELENA-SLEDAI) at baseline, MOS Short Form 36 (SF-36), LupusQoL, and an overall health status item at baseline (D0), 3 (M3) and 6 (M6) months. Self-reported overall health status item enquired about the impact of lupus on overall health since past visit. Its 7 response options were: -3 "much improved", -2 "moderately improved", -1 "minimally improved", 0 "the same", +1 "minimally worse", +2 "moderately worse" and +3 "much worse". Responsiveness and MCID for SF-36 and LupusQoL domains were determined against +1 or -1 change in overall health status (Anchor-based approach). Descriptives and standardized response mean (SRM) of variations in SF36 and LupusQoL domains were estimated and compared using mixed models methods. Results: We included 185 SLE patients. Mean (SD) age and SELENA-SLEDAI were 39.6 (10.6) years and 2.6 (3.5). We analyzed 3 time-point data (515 visits) and two consecutive time-point data (306 visits). LupusQoL "Body Image", "Fatigue", and "Burden to others" domains did not change significantly with "worsening" in overall health status; while LupusQoL "body image", and SF-36 "General Health" and "Physical Functioning" domains did not change significantly with an "improvement" in overall health status. SRM in comparable domains of SF-36 and LupusQoL were similar, except for improvement in LupusQoL Physical Health. SRM ranged from small-moderate for all domains on both measures (table ). Conclusions: Both SF-36 and LupusQoL show responsiveness in most domains with change in overall health status. LupusQoL is more responsive to improvement, while SF-36 is more responsive to worsening in overall health status. Disclosure of Interest: H. Devilliers Consultant for: GlaxoSmithKline, Z. Amoura Consultant for: Amgen, Bristol-Myers Squibb, GlaxoSmithKline, Merck, Neovacs, Roche, Teva Pharmaceuticals, and UCB Pharma, S. Audia: None Declared, M. Jolly Consultant for: GSK, Medimmune, P. Bielefeld: None Declared, L. Arnaud Consultant for: Amgen, C. Binquet: None Declared, J.-F. Besancenot: None Declared